Structure and stability of aluminium trihydroxides bayerite and gibbsite: A quantum mechanical ab initio study with the CRYSTAL06 code - Demichelis, Raffaella; Civalleri, B.; Noel, Y.; Meyer, A.; Dovesi, R. (Elsevier, 2008)
The structure and energetics of bayerite and gibbsite have been investigated at the periodic ab-initioquantum-mechanical level by using a Gaussian type basis set and the B3LYP Hamiltonian.Both systems have layered structure, with intra-layer and inter-layer hydrogen bonds (HBs). In gibbsitethe latter are stronger than in bayerite: 23.15 and 17.59 kJ/mol, respectively. The formation Gibbs freeenergy has been calculated, including entropic and enthalpic contributions: at 298 K gibbsite is more stable than bayerite by 7.74 kJ/mol.